PENERAPAN ART THERAPY UNTUK MENGURANGI KECEMASAN MAHASISWA USIA EMERGING ADULTHOOD PADA MASA PANDEMI - Tjugito, Bryan; Satiadarma, Monty P.; Subroto, Untung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Coronavirus disease 2019 (covid-19) has made major changes for the country in various sectors, one of which is education. Changes that occur in the education sector are in the form of a face-to-face learning system into an online learning system. This change creates anxiety among students. Some of the effects of this anxiety include sleeping difficulties, stomach disorders, and irregular menstrual cycles. Art therapy has been found to significantly reduce the severity of anxiety. Thus, this study aims to determine whether the application of art therapy can reduce anxiety symptoms in students aged 18-25 years who are doing online learning during a pandemic. The research design used in this study was a quasi-experimental. The sampling technique is non-probability sampling by providing a state-trait anxiety inventory (STAI) measurement tool to see the level of anxiety and participants are selected if they are included in the moderate or high category. Six of the twelve participants were selected (4 participants with a moderate level and 2 participants with a high level) and the researcher took individual data by interviewing to help researchers in building rapport with participants. After six intervention sessions, it was found that there was a decrease in anxiety levels, four participants were at low anxiety levels. Coronavirus disease 2019 (covid-19) memberikan perubahan yang besar bagi negara diberbagai sektor, salah satunya pendidikan. Perubahan yang terjadi pada sektor pendidikan berupa sistem belajar tatap muka menjadi sistem belajar daring. Perubahan ini menimbulkan rasa cemas pada para pelajar, tidak terkecuali mahasiswa. Beberapa dampak dari rasa cemas ini berupa sulit tidur, gangguan lambung, hingga siklus haid tidak teratur. Art therapy ditemukan dapat mengurangi kecemasan secara signifikan. Sehingga, penelitian ini memiliki tujuan untuk mengetahui apakah penerapan art therapy dapat mengurangi simtom kecemasan pada mahasiswa berusia 18-25 tahun yang melakukan pembelajaran daring pada masa pandemi. Desain penelitian yang digunakan dalam penelitian ini adalah kuasi eksperimen. Teknik pengambilan sampel non-probability sampling dengan memberikan alat ukur state-trait anxiety inventory (STAI) untuk melihat tingkat kecemasan dan partisipan diseleksi apabila termasuk dalam golongan moderate atau high. Enam dari dua belas partisipan terpilih (4 partisipan dengan tingkat moderate dan 2 partisipan dengan tingkat high) dan peneliti melakukan pengambilan data individual dengan wawancara untuk membantu peneliti dalam membangun rapport dengan partisipan. Setelah enam sesi intervensi, ditemukan bahwa terdapat penurunan pada tingkat kecemasan, empat partisipan berada pada tingkat kecemasan low.